Chapter Measuring economic inequality in Southern Europe: the Iberian Peninsula in the 14th-17th centuries - Chismol, Guillem (Datini Studies in Economic History, 2020)
This work explores the inequality of wealth in Spain during the late Middle Ages from six cities located in the kingdoms of Castile (Seville) and the Crown of Aragon (Barcelona, Valencia, Mallorca, Castelló and Valls), through tax sources that inform about the wealth of each taxpayer. These records provide very precise data on the wealth distribution that allow us to study inequality in an aggregate manner for the same city and, at the same time, perform sectoral analyses according to gender, different socio-professio¬nal groups and urban districts.